The secrets beneath - Fuller, Kathleen (Nashville : Tommy Nelson, 2010)
Curious thirteen-year-old Bekah Yoder wonders about the strange behavior of the man who moves into the house next door, but even she does not suspect the danger that he brings to their neighborhood.
Keywords: Family life -- Ohio -- Fiction; Amish -- Fiction; Neighbors -- Fiction; Cousins -- Fiction; Mystery and detective stories; Middlefield (Ohio) -- Fiction